Komparasi Media Audio-Visual dan Media Kartu dalam Pembelajaran Bahasa Arab - Siti Khamidatul Mutayasiroh (An-Nuqthah, 2021)
Arabic has not shifted from the notion of a difficult language to learn. The factor of the way educators teach is the trigger for this assumption to begin. It is necessary to have media that bridges the learning process, such as audio-visual media and card media. This article aimed to find a comparison of learning Arabic between using audio-visual media and card media in class VII I MTs As-Sunniyyah Kencong Jember. This type of research was a qualitative method. The results of this study indicated that the use of card media could attract students' interest. While the use of audio-visual media could increase students' understanding and students were more enthusiastic in participating in Arabic learning. This shows that the use of learning media is needed in the learning process because it can help in creating an effective, active, and fun class.